Utilization of low-melting temperature alloy with confined seal for reducing thermal contact resistance. (25th December 2019) - Chu, Wen-Xiao; Tseng, Po-Hsiang; Wang, Chi-Chuan
Highlights: Thermal interface materials (TIMs) to reduce thermal contact resistance are carried out. The TIM includes solid-state soft metal and low-melting temperature alloy (LMTA). An apparent hysteresis may occur after loading/unloading contact pressure. The molten LMTA under can effectively reduce the TCR but is prone to overflow. The overflow and dislocation problems of LMTA are solved by a novel confined design. Abstract: This paper investigates a novel design of thermal interface material (TIM) using low-melting temperature alloy (LMTA) with confined seal. For solid TIM like indium foil, the thermal contact resistance is reduced with the rise with contact pressure, and an apparent hysteresis phenomenon may occur during loading/unloading of contact pressure. For the solid-state TIM, the indium TIM outperforms those of copper, lead and tin TIMs. The molten LMTA can further reduce the thermal contact resistance, however, the overflow and dislocation problems are observed. Hence, a novel confined design by using LMTA with an annular metal seal is proposed that can completely prevent aforementioned problems. Yet the reliability of the novel TIM is also investigated after hundred thermal cycles.